Exploring equity and inclusion in Malawi's National Disability Mainstreaming Strategy and Implementation Plan - Ikenna D. Ebuenyi; Emma M. Smith; Alister Munthali; Steven W. Msowoya; Juba Kafumba; Monica Z. Jamali; Malcolm MacLachlan (BMC, 2021)
Abstract Background Equity and inclusion are important principles in policy development and implementation. The aim of this study is to explore the extent to which equity and inclusion were considered in the development of Malawi's National Disability Mainstreaming Strategy and Implementation Plan. Methods We applied an analytical methodology to review the Malawi's National Disability Mainstreaming Strategy and Implementation Plan using the EquIPP (Equity and Inclusion in Policy Processes) tool. The EquIPP tool assesses 17 Key Actions to explore the extent of equity and inclusion. Results The development of the Malawi National Disability Mainstreaming Strategy and Implementation Plan was informed by a desire to promote the rights, opportunities and wellbeing of persons with disability in Malawi. The majority (58%) of the Key Actions received a rating of three, indicating evidence of clear, but incomplete or only partial engagement of persons with disabilities in the policy process. Three (18%) of the Key Actions received a rating of four indicating that all reasonable steps to engage in the policy development process were observed. Four (23%) of the Key Actions received a score five indicating a reference to Key Action in the core documents in the policy development process. Conclusions The development of disability policies and associated implementation strategies requires equitable and inclusive processes that consider input from all stakeholders especially those whose wellbeing depend on such policies. It is pivotal for government and organisations in the process of policy or strategy development and implementation, to involve stakeholders in a virtuous process of co-production - co-implementation - co-evaluation, which may strengthen both the sense of inclusion and the effectiveness of the policy life-cycle.